Word selection in teaching Arabic vocabulary for lower secondary level - Hasmam, Aisah; Nik Yusoff, Nik Mohd Rahimi; Mustapha, Nik Farhan; Kamarudin, Mohd Yusri (Scientific Research Publishing, 2016)
Selecting words for teaching vocabulary is an important part of the teaching and learning of a language. The study aims to explore teacher approach and practice in choosing words for teaching Arabic language at the Lower Secondary Level. A qualitative single case study is used to investigate a phenomenon in the context of the actual situation. Data collection process involve s interviews, classroom observation, video recording and analysis of relevant documents. A purposive sampling method is carried out for selection of participants. The findings indicate that the approach used in selecting vocabulary can be divided into five categories: i) priority ; ii) frequency; iii) teaching ability ; iv) coverage; and v) familiarity. In other words, it is suggested that in facilitating student comprehension and retention of target words, various criteria are considered by a teacher before choosing the teaching approach. The study also provides guidelines for choosing words to teach especially for Arabic teachers in the Lower Secondary Level.